Oxalate loading test: a screening test for steatorrhoea. Issue 12 (December 1979) - Rampton, D S; Kasidas, G P; Rose, G A; Sarner, M
Abstract : To investigate the possibility of measuring urinary oxalate output instead of faecal fat excretion as an outpatient screening test for steatorrhoea, we determined 24 hour urinary oxalate and five day faecal fat excretion before and during an oral load of sodium oxalate 600 mg daily (oxalate 4.44 mmol), in 32 patients with suspected malabsorption on a diet containing oxalate 30 mg (0.33 mmol), fat 50 g (180 mmol), and calcium 1 g (25 mmol). Nineteen patients proved to have steatorrhoea (mean faecal fat 62 mmol/24 h, range 19–186 mmol) of varying aetiologies. On the diet alone, urinary oxalate was raised in only nine of these patients (mean 0.25 mmol/24 h, range 0.08–0.59 mmol) (normal less than 0.20). By contrast, when the diet was supplemented with oral sodium oxalate, all 19 patients with steatorrhoea had hyperoxaluria (mean 0.91 mmol/24 h, range 0.46–1.44 mmol) (normal less than 0.44). There was a significant positive linear relationship between urinary oxalate and faecal fat when the 32 patients were on the high oxalate intake (r = 0.73, P less than 0.001), but not when they were on the low oxalate intake. Mean percentage absorption of orally administered oxalate was 5.8 +/- 0.99% (+/- 1 SD) in normal subjects and 14.7 +/- 6.0% (P less than 0.002) in patients with steatorrhoea. Measurement of urinary oxalate output during oral sodium oxalate loading appears to be a reliable and convenient screening test for steatorrhoea.